MENINGKATKAN KARAKTER PESERTA DIDIK MELALUI PENDIDIKAN AGAMA HINDU DI PASRAMAN: - - I Wayan Sugara Yasa (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
Abstract Education is a conscious effort made by a group of people to educate people from not knowing to knowing which is done by means of a learning process that enables students to actively develop a religious spirit of self-discipline, character, intelligence, noble character, and skills. Pasraman as a form of Hindu religious education has received legal legality in the implementation of Hindu religious education. The goal is that the implementation of religious education in the form of pasraman can be carried out properly according to the mandate of government regulations. Character is a natural attitude that exists in a person that distinguishes it from others.